2013
DOI: 10.18632/oncotarget.863
|View full text |Cite
|
Sign up to set email alerts
|

DNA-intercalators Causing Rapid Re-expression of Methylated and Silenced Genes in Cancer Cells

Abstract: Epigenetic inactivation of tumor-suppressor and other regulatory genes plays a critical role in carcinogenesis. Transcriptional silencing is often maintained by DNA methyl transferase (DNMT)-mediated hypermethylation of CpG islands in promoter DNA. Nucleoside analogs including azacytidine and decitabine have been used to inhibit DNMT and re-activate genes, and are clinically used. Their shortcomings include a short half-life and a slow onset of action due to required nucleotide incorporation during DNA replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…Multiple structure affinity relationship studies have further demonstrated that flavones are capable of intercalating into DNA duplexes [ 44 , 45 ]. The planarity of the benzopyrone skeleton of flavones allows them to easily intercalate the DNA helixes compared to other less planar and non-polar flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple structure affinity relationship studies have further demonstrated that flavones are capable of intercalating into DNA duplexes [ 44 , 45 ]. The planarity of the benzopyrone skeleton of flavones allows them to easily intercalate the DNA helixes compared to other less planar and non-polar flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…S7). Moreover, DNA methyltransferase 1 (DNMT1) plays an important role in maintaining DNA methylation patterns [25,26], Shukla showed that DNMT1 was a transcriptional target of BRCA1 [27]. Our recent study confirmed that DNMT1 mRNA and protein were decreased in BRCA1 -mutated breast cancer.…”
Section: Discussionmentioning
confidence: 53%
“…70 To develop DNA ligands as inhibitors of DNA methylation, it is important to keep in mind the need for selectivity towards CpG islands and, ideally, tumor suppressor promoters that are hypermethylated in cancer. Compound 7 (Figure 2) was rationally designed from a family of minor groove binders.…”
Section: / Update On the Identified Inhibitorsmentioning
confidence: 99%